Insight Into Regulatory T Cells in Sepsis-Associated Encephalopathy - Gao, Yu-lei; Liu, Yan-cun; Zhang, Xiang; Shou, Song-tao; Chai, Yan-fen (Frontiers in Neurology, 2022)
Sepsis-associated encephalopathy (SAE) is a diffuse central nervous system (CNS) dysfunction during sepsis, and is associated with increased mortality and poor outcomes in septic patients. Despite the high incidence and clinical relevance, the exact mechanisms driving SAE pathogenesis are not yet fully understood, and no specific therapeutic strategies are available. Regulatory T cells (Tregs) have a role in SAE pathogenesis, thought to be related with alleviation of sepsis-induced hyper-inflammation and immune responses, promotion of T helper (Th) 2 cells functional shift, neuroinflammation resolution, improvement of the blood-brain barrier (BBB) function, among others. Moreover, in a clinical point of view, these cells have the potential value of improving neurological and psychiatric/mental symptoms in SAE patients. This review aims to provide a general overview of SAE from its initial clinical presentation to long-term cognitive impairment and summarizes the main features of its pathogenesis. Additionally, a detailed overview on the main mechanisms by which Tregs may impact SAE pathogenesis is given. Finally, and considering that Tregs may be a novel target for immunomodulatory intervention in SAE, different therapeutic options, aiming to boost peripheral and brain infiltration of Tregs, are discussed.